Protothecosis in Dogs: A Narrative Review - Jagielski, Tomasz; Proskurnicka, Angelika; Iskra, Mateusz; Wronka, Sylwia; Bakuła, Zofia; Danesi, Patrizia; Farias, Marconi Rodrigues; Ramos Portilho, Fábio Vinícius; Garcia Ribeiro, Márcio; Rösler, Uwe; Kano, Rui; Malik, Richard (Journal of veterinary internal medicine, 2025)
ABSTRACT Protothecosis is a rare and unusual disease that affects both humans and animals, including dogs. The causative agents are unicellular, achlorophyllous, “yeast‐like” microalgae of the genus Prototheca (Trebouxiophyceae, Chlorophyta). Although usually saprophytic, Prototheca may, under conditions of immunologic compromise, become pathogenic and even lethal to the host. We present a synthesis of the current literature on protothecosis, with special emphasis on disease features in the dog. Five open‐access scientific journal repositories were searched two times by two independent reviewers for original studies (including case reports, standard articles, and conference s) pertaining to cases of protothecosis in dogs. Findings about protothecosis cases in dogs (e.g., animal metrics, type of infection, implemented treatment, and treatment outcome) were synthesized in independent data tables. Eighty studies describing 125 cases of protothecosis in dogs qualified for final analysis. Based on this investigation, protothecosis in dogs can be defined as an emerging disease that poses a serious challenge to the veterinary profession in terms of both diagnosis and management. In general, clinical signs and physical findings most often are referable to the gastrointestinal tract (n = 68; 54.4%). Yet the most common clinical manifestation in dogs is disseminated systemic infection (n = 84; 67.2%), including clinical signs referable to inflammation affecting more than one organ. We emphasize the complexity of Prototheca infection in dogs by summarizing clinical and laboratory findings from 125 cases of Prototheca infection in dogs published over the last half‐century.